Oxidative stress and skeletal muscle in exercise - Castrogiovanni, Paola; Imbesi, Rosa (Italian Journal of Anatomy and Embryology, 2012)
Reactive oxygen species (ROSs) are often associated with damage to cellular functions. ROSs production is indicatives of oxidative stress during physical exercise. Oxidative stress occurs in those circumstances in which free radicals determine a tissue damage or production of toxic and dangerous compounds for tissues. In a relaxation state, antioxidant defense of body may hold under control free radicals. Physical activity promotes specific adaptations in relation to type, intensity and duration of physical exercise performed, and a cytoprotective response in skeletal muscle is the increased production of heat shock proteins (HSPs). In ageing, skeletal muscle shows a series of deteriorations, and numerous data suggest that redox processes may play an important role in ageing processes.